Advocacy communication by Never Okay Project on sexual violence in the workplace - Bernard, Kevin Michael; Maryani, Eni (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
Sexual violence in the workplace in Indonesia continues to occur due to various factors. Never Okay Project became one of the organizations that seeks advocacy communication to increase participation of the actors involved and to influence company policies regarding sexual violence. This study aims to explore the advocacy communication carried out by Never Okay Project on sexual violence in the workplace. This research uses a qualitative approach with a case study method. Data within this research was obtained through interviews with organization manager, employer, advocacy targets, and issue observers, as well as observations of advocacy communication contents shared through various channels. Data were analyzed using framework analysis technique (Ritchie et al., 2003). The results of this study show that Never Okay Project was formed as a platform to elevate the stories and experiences of survivors into something worth taking into account. In their efforts of advocacy communication, Never Okay Project is oriented towards workers’ experiences in raising various issues related to sexual violence in the workplace, workers’ experiences and rights, as well as the coverage in various work sectors. Collaboration with various stakeholders as well as Never Okay Project’s advocacy communication with employers has implications towards the formation and improvement of company policies regarding sexual violence in the workplace with more of a survivor’s perspective. This research maps the position of Never Okay Project in raising issues, influencing policies, and developing public participation regarding the issue of sexual violence in the workplace through advocacy communications.